LINE-1 methylation status in prostate cancer and non-neoplastic tissue adjacent to tumor in association with mortality. Issue 1 (2nd January 2017) - Fiano, Valentina; Zugna, Daniela; Grasso, Chiara; Trevisan, Morena; Delsedime, Luisa; Molinaro, Luca; Gillio-Tos, Anna; Merletti, Franco; Richiardi, Lorenzo
ABSTRACT: Aberrant DNA methylation seems to be associated with prostate cancer behavior. We investigated LINE-1 methylation in prostate cancer and non-neoplastic tissue adjacent to tumor (NTAT) in association with mortality from prostate cancer. We selected 157 prostate cancer patients with available NTAT from 2 cohorts of patients diagnosed between 1982–1988 and 1993–1996, followed up until 2010. An association between LINE-1 hypomethylation and prostate cancer mortality in tumor was suggested [hazard ratio per 5% decrease in LINE-1 methylation levels: 1.40, 95% confidence interval (CI): 0.95–2.01]. After stratification of the patients for Gleason score, the association was present only for those with a Gleason score of at least 8. Among these, low (<75%) vs. high (>80%) LINE-1 methylation was associated with a hazard ratio of 4.68 (95% CI: 1.03–21.34). LINE-1 methylation in the NTAT was not associated with prostate cancer mortality. Our results are consistent with the hypothesis that tumor tissue global hypomethylation may be a late event in prostate cancerogenesis and is associated with tumor progression.